KARAKTERISTIK BAKSO JANTUNG PISANG DAN IKAN PATIN DENGAN METODE PENGEMASAN VAKUM DAN NON-VAKUM PADA SUHU DINGIN - Hamdani, Reza Rizky; Harun, Noviar; Efendi, Raswen (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to understand the method of packaging and cold storage and characteristic changes that occur in banana blossom and catfish meatballs during storage. This study used Factorial Randomized Design with 2 factor treatments, cold storage (±0oC, ±5oC, dan ±10oC) and packaging method (vacum and non-vacum) with 3 replications. The treatments in this research include T1M1 (vacuum method at ±0oC), T1M2 (non-vacuum method at ±0oC), T2M1 (vacuum method at ±5oC), T2M2 (non-vacuum method at ±5oC), T3M1 (vacuum method at ±10oC), T3M2 (non-vacuum method at ±10oC). The result of analysis showed that vacuum and non-vacuum method at cold storage was not significantly affect the water content, ash content, protein content, lipid content, total microbial and organoleptic assessment during storage of 2 days, 4 days, and 6 days. The best treatment combination was (T1M1) 6nd day with water content 74,06%, ash content 1,57%, protein content 12,73%, lipid content 4,46%, and total microbial 8,67 x 106  colony/ml.white, slightly slimy appearance, tyish Keywords: Catfish meatball, packaging method, cold storage